Selection of pretreatment method and mannanase enzyme to improve the functionality of palm kernel cake - Sathitkowitchai, Witida; Ayimbila, Francis; Nitisinprasert, Sunee; Keawsompong, Suttipun (Journal of bioscience and bioengineering, 2022)
Palm kernel cake (PKC) is a by-product of palm kernel oil extraction with moderate nutritional value, containing 30-35% β-mannan, which is indigestible, slows growth, and reduces feed efficiency. PKC can be improved by mannanase hydrolysis, but the effectiveness of mannanase is dependent on the microbial source. Thus, the effect of steam pretreatment and bacterial mannanases on PKC quality was investigated. PKC was pretreated by steaming and hydrolyzed in the small intestine by various mannanases. The contents of reducing sugar, total sugar, and protein release were measured. Steamed PKC had a significant increase in protein (16.95 ± 0.14 to 20.98 ± 0.13%) and a substantial decrease in hemicellulose (29.52 ± 0.44 to 3.46 ± 0.88%) and lignin (8.94 ± 0.28 to 1.40 ± 0.22%). Mannanases from Escherichia coli-KMAN-3 and E. coli-Man6.7 recorded the highest activities, followed by commercial mannanase, Bacillus circulans NT6.7 and B. amyloliquefaciens NT6.3 mannanases, orderly. B. circulans NT6.7 and B. amyloliquefaciens NT6.3 had multi-activities that include glucanase (3.10 ± 0.04% and 2.47 ± 0.02%) and amylase (1.74 ± 0.03% and 1.38 ± 0.04%), respectively. B. amyloliquefaciens NT6.3 mannanase hydrolyzed steamed PKC to release more reducing sugar, total sugar, and protein than hydrolyzed raw PKC. In raw and steamed PKC, B. amyloliquefaciens NT6.3 mannanase produced the highest reducing sugar release. As a result, steam pretreatment and mannanase hydrolysis, particularly from B. amyloliquefaciens, can be used to increase the functioning of PKC and develop new feed ingredients for monogastric animals at a reasonable cost.Palm kernel cake (PKC) is a by-product of palm kernel oil extraction with moderate nutritional value, containing 30-35% β-mannan, which is indigestible, slows growth, and reduces feed efficiency. PKC can be improved by mannanase hydrolysis, but the effectiveness of mannanase is dependent on the microbial source. Thus, the effect of steam pretreatment and bacterial mannanases on PKC quality was investigated. PKC was pretreated by steaming and hydrolyzed in the small intestine by various mannanases. The contents of reducing sugar, total sugar, and protein release were measured. Steamed PKC had a significant increase in protein (16.95 ± 0.14 to 20.98 ± 0.13%) and a substantial decrease in hemicellulose (29.52 ± 0.44 to 3.46 ± 0.88%) and lignin (8.94 ± 0.28 to 1.40 ± 0.22%). Mannanases from Escherichia coli-KMAN-3 and E. coli-Man6.7 recorded the highest activities, followed by commercial mannanase, Bacillus circulans NT6.7 and B. amyloliquefaciens NT6.3 mannanases, orderly. B. circulans NT6.7 and B. amyloliquefaciens NT6.3 had multi-activities that include glucanase (3.10 ± 0.04% and 2.47 ± 0.02%) and amylase (1.74 ± 0.03% and 1.38 ± 0.04%), respectively. B. amyloliquefaciens NT6.3 mannanase hydrolyzed steamed PKC to release more reducing sugar, total sugar, and protein than hydrolyzed raw PKC. In raw and steamed PKC, B. amyloliquefaciens NT6.3 mannanase produced the highest reducing sugar release. As a result, steam pretreatment and mannanase hydrolysis, particularly from B. amyloliquefaciens, can be used to increase the functioning of PKC and develop new feed ingredients for monogastric animals at a reasonable cost.